Overexpression of p53 protein in Barrett's syndrome with malignant transformation. Issue 4 (April 1993) - Fléjou, J F; Potet, F; Muzeau, F; Le Pelletier, F; Fékété, F; Hénin, D
Abstract : AIMS--To study the overexpression of p53 protein in Barrett's oesophagus with adenocarcinoma, and to correlate this expression with the pathological features of Barrett's syndrome. METHODS--Immunohistochemical staining was performed on frozen sections with a monoclonal antibody directed against wild type and mutated p53 protein (Pab 1801). Eleven cases of Barrett's adenocarcinoma were studied, seven of which had extensive sampling of benign Barrett's mucosa. RESULTS--Eight of 11 adenocarcinomas overexpressed the p53 protein. Both early and advanced tumours were positive. In Barrett's mucosa around the p53 positive tumours, high grade dysplasia was positive; low grade dysplasia and non-dysplastic mucosa were negative. CONCLUSIONS--P53 gene mutation with ensuing p53 protein overexpression is a common feature of Barrett's adenocarcinoma, both at early and advanced stages. This mutation appears as a relatively late event during the neoplastic transformation of Barrett's oesophagus.